(untitled) (Journal of Hama University, 2024)
The aim of the current research was to identify the degree of possession of the Seventh grade students Problem-solving skills in biology. The sample consisted of (250) students and students, randomly selected from (7) schools in Lattakia. The research is an achievement test for Problem-solving skills. It consists of (18) multiple choice questions and the generation of alternatives. The veracity of the tool has been verified by presenting it to a group of arbitrators. The stability of the tool has been confirmed by a survey sample, (0.70). After applying the tool and analyzing the results, the researcher reached a low level of possession of the Seventh grade students for Problem-solving skills in general. The percentage of proficiency was (52.17%), which is less than the required limit (70%). The results of the study showed that there were varying levels of proficiency of the sample for Problem-solving skills. The sample achieved the level of proficiency in the defining the problem and choosing the best alternative in percentages of (83.87%) and (76.13%) respectively, The percentages of proficiency by percentage(14.93%),. Researcher with a number of relevant proposals to continue the research, the most important of which was: 1_ descriptive study of the role of teachers in the development of Problem-solving skills of students in the basic education stage. 2_ An analytical study of the books of biology in the basic education stage; to know the extent of the inclusion of the Problem-solving skills.